The importance of the pharmacist in the population's health care services: carrying out COVID-19 tests in a drugstore (Research, Society and Development, 2022)
This is an integrative review of the literature on the performance of rapid tests (immunochromatographic tests) in drugstores to aid in the diagnosis of COVID-19 and other activities carried out during the pandemic, in order to demonstrate what contributions are provided in assistance to the population health. The research was carried out through searches in the databases of Scielo, PubMed, Lilac, Periodicos Capes and in official websites containing information on this activity, where twenty-nine articles (29) were selected to compose the results. It was observed that the pharmacist in the pandemic was fundamental in carrying out health promotion actions during the execution of rapid tests for COVID-19 and also acting in measures aimed at communicating ways of safety and preventing the spread of the virus, in addition to providing guidelines to minimize the practice of self-medication in the pandemic.